Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1088/0957-4484/18/20/205503
|View full text |Cite
|
Sign up to set email alerts
|

Fracture strength and Young’s modulus of ZnO nanowires

Abstract: The fracture strength of ZnO nanowires vertically grown on sapphire substrates was measured in tensile and bending experiments. Nanowires with diameters between 60 and 310 nm and a typical length of 2 ñm were manipulated with an atomic force microscopy tip mounted on a nanomanipulator inside a scanning electron microscope. The fracture strain of (7.7 ± 0.8)% measured in the bending test was found close to the theoretical limit of 10% and revealed a strength about twice as high as in the tensile test. From the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(120 citation statements)
references
References 16 publications
6
110
2
Order By: Relevance
“…Contrary to experimental reports of brittle fracture [10, 13,21] (as shown in Figure 3a), atomistic modelling employing a Buckingham-type pairwise force-field revealed stressinduced phase transformation (shown in Figure 3b). Simulations showed that the NWs underwent a phase transformation from original wurtzite (WZ) phase to a body-centered tetragonal (BCT) phase [10, [22][23].…”
Section: Failure Mechanisms In Zno Nanowirescontrasting
confidence: 87%
“…Contrary to experimental reports of brittle fracture [10, 13,21] (as shown in Figure 3a), atomistic modelling employing a Buckingham-type pairwise force-field revealed stressinduced phase transformation (shown in Figure 3b). Simulations showed that the NWs underwent a phase transformation from original wurtzite (WZ) phase to a body-centered tetragonal (BCT) phase [10, [22][23].…”
Section: Failure Mechanisms In Zno Nanowirescontrasting
confidence: 87%
“…15 The remarkable scattering of e FS can thus be attributed to the size distribution of critical defects, and their size effect results from the reduction of critical defects with decreasing D, which is in accordance with previous qualitative reports. [3][4][5][6][7][8] Concerning critical defects, Weibull statistical analysis is promising for revealing their size and spatial distribution a)…”
Section: Resultsmentioning
confidence: 99%
“…As depicted by the Weibull statistics, 2 the expected r FS of specimens increase as their characteristic sizes decrease, a condition known as size effect, which has been the core issue of fracture mechanics since Griffith. 1 Recently, increasing attention paid to the mechanical properties in nanowires (NWs) [3][4][5][6][7][8] and nanotubes (NTs) [9][10][11] is extending the size effect into the nanoscale. Although the defect-dominated r FS in NTs have been well understood based on Griffith's theory 10 and atomistic simulations, 11 for NWs, there were merely some preliminary experimental results on the size effect of r FS .…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Similar effects have been observed for ZnO nanowires with Young's modulus of about 100 GPa, which is 30% lower than the bulk value. 20 For VO x nanotubes, although p and n doping may render the nanotubes ferromagnetic 7 and make them very promising for spin dependent scanning probe applications, the structural perfectness of these tubes has to be improved. In particular, for Li-doped nanotubes, Hellmann et al 21 recently indicated that the structural instability is a major concern.…”
Section: -mentioning
confidence: 99%